MKUKUTA Annual Implementation Report Taking stock of achievements and challenges over the last five years - Ministry of Finance and Economic Affairs (Dar es Salaam MKUKUTA Secretariat, 2010)
MKUKUTA Annual Implementation Report (MAIR) is for the purpose of tracking progress and inform subsequent policy actions and activities as well as informing budget decision and Medium Term Expenditure Framework (MTEF) process. It consolidates and provides a coherent analysis of information from sectors to cluster level, thus facilitating the dialogue among stakeholders for subsequent interventions. The Report also facilitates forging of closer links between Government coordination, monitoring and reporting.
Keywords: Income Poverty